1999
DOI: 10.1074/jbc.274.43.30729
|View full text |Cite
|
Sign up to set email alerts
|

TNIK, a Novel Member of the Germinal Center Kinase Family That Activates the c-Jun N-terminal Kinase Pathway and Regulates the Cytoskeleton

Abstract: Germinal center kinases (GCKs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
190
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(204 citation statements)
references
References 26 publications
(45 reference statements)
11
190
2
1
Order By: Relevance
“…This gene encodes a protein belonging to the mammalian germinal center kinases (GCK) family, interacting Letters to the Editor with both Traf2 and NCK, and able to specifically activate the Jun N-terminal kinase domain pathway. 8 In conclusion, we hypothesize that, following the t(3;12) rearrangement, the translocation of the promoter and the 5 0 portion of TNIK downstream to HMGA2 leads to the activation of the latter gene as a consequence of a position effect. …”
mentioning
confidence: 82%
“…This gene encodes a protein belonging to the mammalian germinal center kinases (GCK) family, interacting Letters to the Editor with both Traf2 and NCK, and able to specifically activate the Jun N-terminal kinase domain pathway. 8 In conclusion, we hypothesize that, following the t(3;12) rearrangement, the translocation of the promoter and the 5 0 portion of TNIK downstream to HMGA2 leads to the activation of the latter gene as a consequence of a position effect. …”
mentioning
confidence: 82%
“…In particular, GCKs of the group II do not stimulate any of the currently known MAPK pathways. 145 Several group I GCKs (germinal center kinase (GCK), 146 GCK-like kinase (GLK), 147 GCK-related (GCKR), 148 HPK/GCK-like kinase (HGK), 149 NIK-like embryo-specific kinase (NESK), 150 TRAF2 and Nck-interacting kinase (TNIK) 151 ) have been implicated in TNF-mediated JNK activation because of the following findings: they become activated by TNF (NESK, HGK, GCKR, GLK), interact with TRAF2 (TNIK, GCK, GCKR 152 ) and dominant-negative mutants of these kinases interfere with TNF-induced JNK activation (NESK, HGK, GCKR). The group I GCKs seem to channel stimulation of TNF-R1 to the JNK cascade by concomitant interaction with TRAF2 and MEKK1 and phosphorylation-dependent activation of the latter.…”
Section: Ap-1mentioning
confidence: 99%
“…For example, the various GCKs, which have been implicated in TNF-induced activation of JNK, are unable to stimulate the p38-MAPK cascade. 147,[149][150][151]161 In addition, it has been shown that a deletion mutant of RIP, lacking its intermediate domain, interferes with TRAF2-mediated activation of p38-MAPK, but failed to inhibit TRAF2-induced JNK activation. 146 Thus, TNF may signal p38-MAPK activation via an axis comprising TRAF2 and RIP, whereas JNK activation occurs via TRAF2-GCKs-MEKK1/ASK1.…”
Section: Ap-1mentioning
confidence: 99%
“…Proline-and alanine-rich STE20-related kinase associates with actin, and prostate-derived STE20-like kinase (PSK), Traf2-and Nckinteracting kinase, and STE20-like kinase (SLK) decrease actin stress fibers and focal adhesions and inhibit cell spreading (3,(13)(14)(15). SLK has recently been shown to associate with MTs at the cell periphery (16).…”
mentioning
confidence: 99%